A non-hypocholesterolemic atorvastatin treatment improves vessel elasticity by acting on elastin composition in WHHL rabbits. (August 2016) - Tissier, Florine; Mallem, Yassine; Goanvec, Christelle; Didier, Romain; Aubry, Thierry; Bourgeois, Nathalie; Desfontis, Jean-Claude; Dubreuil, Matthieu; Le Grand, Yann; Mansourati, Jacques; Pichavant-Rafini, Karine; Plee-Gautier, Emmanuelle; et al.
Abstract: Background and aims: Statins are prescribed for their preventative effects within atherosclerosis development. To our knowledge, no study focusing on very low-dose (non-hypolipidemic effect) and long-term atorvastatin treatment in vivo was available. Our aim was to assess the effect of such atorvastatin treatment on the mechanical and functional characteristics of arteries in the context of primary prevention. Methods: An atorvastatin treatment (2.5 mg/kg/day) was tested against controls on 34 male 3 to 12 month-old WHHL rabbits. No effect on total cholesterol, triglycerides, HDL or LDL was observed. The arterial stiffness was evaluated on vigil animals by pulse wave velocity (PWV) measurement. Then, in vitro measurements were made to evaluate (1) the endothelial and vascular smooth muscle function, (2) the elasticity of the arterial wall and (3) the composition in collagen and elastin in the aorta. Results: The PWV increasing observed with age in control group was canceled by treatment, creating a significance difference between groups at 12 months (5.17 ± 0.50 vs 2.14 ± 0.34 m s −1 in control and treated groups respectively). Vasoreactivity modifications can't explain this result but maintain of elasticity with treatment in large arteries was confirm by a static tensile test. A first possible explanation is the change of wall composition with treatment, validated by the percentage of elastin at 12 months, 4.4% lower in the control group compared to the treated group ( p < 0.05). Conclusions: This study shows that a non-hypocholesterolemic statin treatment could improve vessel elasticity in the atherosclerotic WHHL model. The great novelty of this work is the vessel wall composition changing associated. This first approach in animal opens the reflection on the use of these low doses in humans. This could be interesting in the context of arterial stiffening with aging, non-hyperlipidemic atherosclerosis or with cholesterol reduce by another therapy or lifestyle modification. Highlights: Study about new use of statin, without hypocholesterolemic effects. Protective effects on the large arteries elasticity in WHHL (visible on PWV). Young's modulus measurement confirm structural maintain of elasticity. Modifications visible on intrinsic artery wall composition (elastin content).